2016
DOI: 10.1038/ncomms10213
|View full text |Cite
|
Sign up to set email alerts
|

1,25D3 prevents CD8+Tc2 skewing and asthma development through VDR binding changes to the Cyp11a1 promoter

Abstract: Effector CD8+ T cells convert from IFN-γ+ (Tc1) to IL-13+ (Tc2) cells in the presence of IL-4. Underlying regulatory mechanisms are not fully defined. Here, we show that addition of 1,25D3, the active form of vitamin D3, during CD8+ T-cell differentiation prevents IL-4-induced conversion to IL-13-producers. Transfer of 1,25D3-treated CD8+ T cells into sensitized and challenged CD8+-deficient recipients fails to restore development of lung allergic responses. 1,25D3 alters vitamin D receptor (VDR) recruitment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 63 publications
(133 reference statements)
2
52
0
Order By: Relevance
“…NUMEROUS BENEFICIAL EFFECTS of vitamin D on respiratory health have been reported, including better forced expiratory volume in 1 s (FEV 1 ) (16), decreased asthma susceptibility (31), decreased severity of exacerbations in individuals with chronic obstructive pulmonary disease (COPD) (20), and decreased tuberculosis risk (21). Protective effects may result from a variety of mechanisms including vitamin D-mediated production of antimicrobial peptides, airway remodeling, and modulation of inflammation and immune phenotypes.…”
mentioning
confidence: 99%
“…NUMEROUS BENEFICIAL EFFECTS of vitamin D on respiratory health have been reported, including better forced expiratory volume in 1 s (FEV 1 ) (16), decreased asthma susceptibility (31), decreased severity of exacerbations in individuals with chronic obstructive pulmonary disease (COPD) (20), and decreased tuberculosis risk (21). Protective effects may result from a variety of mechanisms including vitamin D-mediated production of antimicrobial peptides, airway remodeling, and modulation of inflammation and immune phenotypes.…”
mentioning
confidence: 99%
“…VDR, through heterodimerization with the retinoid-X receptor (RXR), then binds to vitamin D response elements (VDREs) in the regulatory region of target genes [(48); Figure 3]. VDREs are normally localized close to the promoter of genes, although evidence from recent research indicates VDR complex can operate over distances of 75 kb to regulate target gene transcription (77), increasing the potential of VDR complexes to regulate our genome (78). There are more than 1,000 genes with binding sites for VDRE, including AMPs such as cathelicidin (79), β-defensin (79), the 25-hydroxyvitamin D 24-hydroxylase ( CYP24 ) gene, and cytochrome P450 family 11 subfamily A ( CYP11A1 ) gene (78).…”
Section: Discussionmentioning
confidence: 99%
“…VDREs are normally localized close to the promoter of genes, although evidence from recent research indicates VDR complex can operate over distances of 75 kb to regulate target gene transcription (77), increasing the potential of VDR complexes to regulate our genome (78). There are more than 1,000 genes with binding sites for VDRE, including AMPs such as cathelicidin (79), β-defensin (79), the 25-hydroxyvitamin D 24-hydroxylase ( CYP24 ) gene, and cytochrome P450 family 11 subfamily A ( CYP11A1 ) gene (78). In fact, ~3% of the mouse and human genomes are regulated directly or indirectly by VDRs (49), which may explain their role on preventing various diseases mechanisms (33), even in the fetal stage [(32); Figure 3].…”
Section: Discussionmentioning
confidence: 99%
“…Asthma has been traditionally associated with an expansion of CD4 + type 2 helper T (Th)-cells in response to allergen exposure and these cells are considered mainly responsible for the disease. Thus, it is not surprising that a correlation between CD4 [11][12][13][14][15][16]. But which subset, or subsets are found in asthma?…”
Section: Second: the Possible Role Of Cd8 + T-cells In Asthmamentioning
confidence: 99%
“…These cells have a potentially important role in dictating the severity of asthma, since IL-13 is a critical mediator of airway hyperresponsiveness and mucus hyperproduction, and CD8 + Tc2-cells seem to be fairly resistant to corticosteroids treatment. There might be some positive news about these IL-13-producing CD8 + T-cells, since it was recently shown that vitamin D can downregulate the conversion of CD8 + T-cells into IL-13-producing Tc2-cells mediated by IL-4, thus being beneficial to asthmatic subjects [14]. Further studies targeting this subset of CD8 + T-cells would be necessary to establish their causative role in asthma.…”
Section: Could These Cd8mentioning
confidence: 99%